Adversity and risk of poor birth and infant outcomes for young mothers: a population-based data-linkage cohort study. (November 2016) - Harron, Katie; Gilbert, Ruth; Cromwell, David; Oddie, Sam; van der Meulen, Jan
Abstract: Background: Maternal health behaviours and psychosocial factors are associated with poor birth outcomes and increased hospital admissions throughout childhood. We aimed to assess birth and infant outcomes according to maternal age and adversity indicators using population-level health-care data. Methods: We extracted linked maternity–baby hospital data from Hospital Episode Statistics for births between 2009 and 2012 in England. Indicators of maternal adversity were identified with International Classification of Diseases 10th revision diagnosis codes for drug or alcohol misuse, violence, or self-harm from any hospital admission up to 2 years before delivery. Mothers were categorised as current young (<21 years at current birth), prior young (<21 at first birth but not current birth), or never young (≥21 at first birth). Multivariable regression (with adjustment for additional maternal and baby risk-factors including deprivation) was used to determine the association between maternal exposures and preterm birth (<37 weeks' gestation), low birthweight (<2500 g), and unplanned re-admissions and deaths within 12 months after discharge from the birth episode. Findings: 138 875 (8·5%) of 1 636 019 mothers were current young and 144 168 (8·8%) were prior young mothers. Adversity indicators in the 2 years before delivery were identified for 108 131 (6·6%) mothers, rising to 21 487 (15·5%) for current and 21 237 (14·7%) for prior young mothers. Adversity was the most important risk factor for the immediate birth outcomes of preterm birth and low birthweight (odds ratio [OR] 1·53, 95% CI 1·46–1·60 [p<0·0001] and 1·97, 1·89–2·06 [p<0·0001], respectively). By contrast, maternal age was most important for infant outcomes (OR for re-admission, current young 1·53, 1·47–1·58 [p<0·0001] and prior young 1·40, 1·35–1·44 [p<0·0001]) compared with never young mothers. Risk of infant mortality was increased for current compared with never young mothers (OR 1·37, 1·18–1·60; p<0·0001) and for mothers with adversity (1·22, 1·05–1·42; p=0·021). Interpretation: Although linked, young maternal age and adversity affect infant outcomes in different ways. Indicators of adversity in the 2 years before birth are important exposures for immediate birth outcomes, whereas young maternal age at first birth (irrespective of current age) is an important risk-factor for poor outcomes during infancy. A major strength of this study is the use of a national linked dataset, although under-ascertainment of adversity in Hospital Episode Statistics could lead to an underestimation of risk. Funding: Wellcome Trust (grant number WT103975/Z/14/Z).